Community-Based Total Sanitation Health Promotion Strategy in Kebaman Village, Srono District, Banyuwangi Regency - Ratih Eka Fitrianingrum (Journal for Quality in Public Health, 2020)
Sanitation is an important study because it is one of the fundamental aspects of human rights and has a broad impact when sanitation development is neglected. The problem of sanitation is not just a matter of building sanitation facilities and infrastructure but a problem of community hygiene. The purpose of this study is to describe the strategy of promoting community-based Total Sanitation (STBM) health in Kebaman Village, Srono District, Banyuwangi Regency. This research is a qualitative study and was carried out on 1-27 July 2019 in Kebaman Village, Srono District, Banyuwangi District. The subjects of this study were all who were involved in this study including the main informants namely youth clubs, community leaders, and CBTS cadre and triangulation informants from Kebaman Village residents and PKM Kebaman sanitarians. Data collection in this study uses interview guidelines with semi-structured questions using mobile media to record and document. The results showed that the commitment to the implementation of the STBM program in the village of Kebaman had not been maximized as a whole because socialization and coordination to those who could support the implementation of the STBM program had not been fully carried out maximally and community empowerment of the STBM program through triggering had never been carried out. reaching all levels of society so there is a need for socialization and coordination with cross-sectoral and cross-program collaboration